EFFECTIVENESS OF COMMUNICATION TOOLS IN ROAD TRANSPORTATION: NIGERIAN PERSPECTIVE - Adedeji, Jacob Adedayo; Abejide, Samuel Olugbenga; Hassan, Mohamed Mostafa (International Conference on Traffic and Transporet Engineering- Belgrade November 24-25, 2016)
Continuous increase in death toll as a result of road accident is at an alarming rate. Recent World Health Organization (WHO) global annual report estimated that about 1.25 million people die in road crashes and Africa region as the highest contributor. This traffic fatality rate has, however, been associated with poor roads condition, drink-driving, over speeding, violation of traffic rules, and careless attitude of the road users. Over the years, various measures such as rehabilitation of poor roads and traffic regulations …etc., has been put in place to avert this predicament but the reverse is the case as death toll through road accident increases by years. Additional measures also include the use of traffic communication tools. Although various communication tools exist on the road, this ought to guide the road users and in a way avert the dangers upcoming; however, this is not the case. In Nigeria, various studies have been conducted to this regards but little or no attention is given to the road marking as a communication tool, thus, these three question remains for Nigeria road network; (1) Do these tools (especially, road marking) exist on roads where accidents are frequent? (2) Are these tools effective? (3) What is the understanding of the road users of these tools? Therefore, this study pertains to the effectiveness of the communication tools in road transportation by considering the Nigeria road features and views of the road users. Results show that the drivers have a good knowledge of these traffic communication tools but on an average of 92%, the road marking sampled are not available on the roads and have in one way or the other contributed to the fatality rate experienced. There is a need for stakeholder’s interventions which include regular funding and schedule for routine maintenance with more focus on road marking.
Published Conference Proceedings
Keywords: traffic fatality; traffic communication tools; road marking; traffic safety; Nigeria roads